A Fifteen Years Audit of Endometrial Cancer Referred for Adjuvant Treatment to a Tertiary Care Hospital in Northern India - Pramod Kumar Gupta; Shalini Singh; Rupali Gupta; Punita Lal; Neeraj Rastogi (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Endometrial cancer is the seventh most common cancer in women worldwide with Age Standardised Incidence Rate (ASIR) of 8.4 per lac. In Indian subcontinent, the incidence is lesser and the ASIR is 2.1/100,000 women. However, its incidence is on the steady rise in developing part of the world including India. Surgery is the primary treatment and adjuvant radiotherapy is given in patients with high-risk of recurrence and significant change has happened in the management in the last 20 years. From India limited literature is available for management practices for endometrial cancer. Aim: To assess the referral patterns, demography, staging, surgical practices, adjuvant treatment and follow-up policies for endometrial cancer in a tertiary care hospital in northern India. Materials and Methods: A retrospective cross-sectional study was done for patients having endometrial cancer treated between January 2000- December 2015 in a tertiary care hospital in northern India in January 2022. A total of 93 patients having endometrial cancer were referred for radiotherapy. For these patients, their referral patterns, demography, staging, surgical practices, adjuvant treatment and follow-up policies were analysed, retrospectively. Disease Free Survival (DFS) and Overall Survival (OS) were computed by Kaplan-Meier method. Results: The median age at presentation was 55 years. Postmenopausal vaginal bleeding was the commonest symptom 78 (83.87%). Ultrasonography 23 (24.73%) was the preferred first imaging modality. Type 1 endometroid carcinoma was 75 (80.64%) and total abdominal hysterectomy with bilateral salpingo-oophrectomy was done in 82 (88.17%). Adjuvant External Beam Radiotherapy (EBRT) with Brachytherapy (BT) was given in 61 (65.59%), EBRT alone in 7(7.52%) and BT alone given in 11 (11.83%). Median EBRT dose was 50.4 Gy. Vaginal cylinder applicator was used in 69 (95.83%) out of 72 patients receiving BT. A 6.0 Gy/# to a total of 2 fractions were given in 57 (79.16%). Median treated length of vagina was 3 cm (range 2-8 cm). Five year DFS and OS was 25% and 25% and 64% and 62% respectively in worst and best case scenario. Ten (10.75%) patients, all having high-risk had multiple visceral and local recurrence. Conclusion: In patients with endometrial cancer, total abdominal hysterectomy with bilateral salpingo-oophrectomy is commonest surgical practice with adjuvant radiotherapy in high-risk patients. In a developing country like India, assuring uniformity of treatment protocols is a challenging task.